Leisure-Time Physical Activity in People With Spinal Cord Injury-Predictors of Exercise Guideline Adherence - Paul K. Watson; Mohit Arora; Mohit Arora; James W. Middleton; James W. Middleton; Camila Quel de Oliveira; Robert Heard; Andrew Nunn; Timothy Geraghty; Timothy Geraghty; Ruth Marshall; Ruth Marshall; et al. (Frontiers Media S.A., 2022)
Objectives: This study described leisure-time physical activity (LTPA) for people in Australia with spinal cord injury (SCI) and whether certain sociodemographic and psychosocial variables might be associated with LTPA uptake and guidelines adherence.Methods: The Physical Activity Scale for Individuals with a Physical Disability was used to measure the intensity and volume of LTPA of 1,579 individuals with SCI. Summary statistics were calculated for LTPA guidelines adherence. Analyses included regression modelling.Results: Of the 1,579 participants, 58% performed LTPA and 13% adhered to recommended guidelines for weekly LTPA. There was an association with being an "exerciser" based on the time since injury (OR = 1.02 [95% 1.01-1.03]), a traumatic injury (OR = 1.53 [95% CI 1.13-2.08]) and a higher self-rating of health (OR = 1.10 [95% CI 0.95-1.27]). Where LTPA guidelines were met, adherence was most related to a traumatic injury (OR = 1.75 [95% CI 1.02-3.02]) and being unemployed (OR = 1.53 [95% CI 1.03-2.25]).Conclusion: Of those who performed LTPA with SCI, one in four met population-specific LTPA guidelines. Sociodemographic variables were moderately associated with being an "exerciser" or LTPA "guideline-adherent."